Carotenoid-Rich Brain Nutrient Pattern Is Positively Correlated With Higher Cognition and Lower Depression in the Oldest Old With No Dementia - Tanprasertsuk, Jirayu; Scott, Tammy M.; Barbey, Aron K.; Barger, Kathryn; Wang, Xiang-Dong; Johnson, Mary Ann; Poon, Leonard W.; Vishwanathan, Rohini; Matthan, Nirupa R.; Lichtenstein, Alice H.; Ferland, Guylaine; Johnson, Elizabeth J. (Frontiers in Nutrition, 2021)
Background: Healthy dietary patterns are related to better cognitive health in aging populations. While levels of individual nutrients in neural tissues are individually associated with cognitive function, the investigation of nutrient patterns in human brain tissue has not been conducted. Methods: Brain tissues were acquired from frontal and temporal cortices of 47 centenarians from the Georgia Centenarian Study. Fat-soluble nutrients (carotenoids, vitamins A, E, K, and fatty acids [FA]) were measured and averaged from the two brain regions. Nutrient patterns were constructed using principal component analysis. Cognitive composite scores were constructed from cognitive assessment from the time point closest to death. Dementia status was rated by Global Deterioration Scale (GDS). Pearson’s correlation coefficients between NP scores and cognitive composite scores were calculated controlling for sex, education, hypertension, diabetes, and APOE ε4 allele. Result: Among nondemented subjects (GDS=1-3, n=23), a nutrient pattern higher in carotenoids was consistently associated with better performance on global cognition (r=0.38, p=0.070), memory (r=0.38, p=0.073), language (r=0.42, p=0.046), and lower depression (r=-0.40, p=0.090). The findings were confirmed with univariate analysis. Conclusion: Both multivariate and univariate analyses demonstrate that brain nutrient pattern explained mainly by carotenoid concentrations is correlated with cognitive function among subjects who had no dementia. Investigation of their synergistic roles on the prevention of age-related cognitive impairment remains to be performed.